The association of spongivore reef fish to benthos attributes - Deocadez, Melchor R. (Institute of Environmental Science and Meteorology, College of Science, University of the Philippines Diliman, 2013)
This study seeks to investigate the distribution of spongivore reef fish and their relation to ecological and environmental attributes of selected Philippine coral reefs.